Risks of Glacial Lakes Under Climate Change - B. T., Ibragimov; D. M, Zhunsaliev (European Journal of Life Safety and Stability (2660-9630), 2022)
Glacial lakes are characteristic landscape elements in mountains, comprising a variety of potential uses, but at the same time posing a potential risk to humans and infrastructure downstream. Wth the continued retreat of glaciers, new glacial lakes will form in glacierized mountain regions worldwide during the coming decades. A sustainable approach to deal with both the risks and opportunities provided by such lakes requires a long-term, integral planning, which considers besides geo-technical aspects also socio-economic factors and developments. This article discusses the impact of global climate change on the stability of mountain glaciers and lakes, the nature of natural hazards resulting from this change, as well as the relevance and prospects of studying mountain glaciers and lakes